A Versatile General Multiplier Divider Cell by Using Operational Trans-Resistance Amplifiers - Khachab, Nabil I.; Cherri, Abdallah; Hayssam, Ahmad (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2017)
In this paper, we present the design of a versatile general multiplier-divider cell by using the Operational Trans-resistance Amplifier (OTRA) and MOSFETs operating in the linear region. The design and the basic operation of this block is verified. Other operations can also be realized by simply choosing the inputs of the signals at the different terminals. These operations include square root operation, scalar vector multiplier and modulation to name a few. The new cell is reconfigurable and can be programmed by DC voltages. The resulting circuits are simulated by 0.18 m CMOS process through PSPICE. These simulation results verify the versatile operation of this cell.